The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.3329/jbau.v8i2.7945
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of floodplain aquaculture at Daudkandi upazilla in Comilla

Abstract: An economic anylysis was made to determine the cost of fish production in the floodplains at Daudkandi Upazilla in Comilla district during the period form January to April, 2007. Survey method was followed to collect data from 20 floodplain aquaculture projects. The projects record books and personal interviews of the NGOs and Fisheries officers were the main instruments of data collection. Statistical tools such as: range, mean, standard deviation and percentage were employed for analysis of data. The Cobb-Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…Total fish production for the six months culture periods was 2622.15 kg/ha. Chandra et al (2010) recorded 2920.43 kg/ha fish production in beel aquaculture from Daudkandi, Cumilla, Bangladesh which is higher than the production of present study. The parasitic infection could be linked with the lower fish production in the present study as compared to the earlier study.…”
Section: Fish Health Managementcontrasting
confidence: 69%
“…Total fish production for the six months culture periods was 2622.15 kg/ha. Chandra et al (2010) recorded 2920.43 kg/ha fish production in beel aquaculture from Daudkandi, Cumilla, Bangladesh which is higher than the production of present study. The parasitic infection could be linked with the lower fish production in the present study as compared to the earlier study.…”
Section: Fish Health Managementcontrasting
confidence: 69%
“…According to Bayley (1988) the maximum potential yields is more highly exploited tropical floodplains at 110-160 kg/ha/yr. Most of the floodplains in Bangladesh are not cultured in a plan way as like as Daudkandi area floodplain shown by recent research (Chandra et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…3389.82/ha on average which was 1.62 % of the total investment for fish culture purposes in Khirai floodplain whereas it was 3.45 % in Angrail floodplain. According to Chandra et al (2010), as the floodplain area had lower land elevation, it became flooded regularly depending on the water level in the adjacent rivers. For aquaculture project to select floodplain area, it required encircling the area by constructing good embankment and sluice gates.…”
Section: Marketing Of Fishmentioning
confidence: 99%
“…The productivity of the chaur was 243.81 kilogram per hectare per year. Chandra et al (2010) found average fish production of 2920.43 kilogram per hectare per year from beels of Bangladesh whereas production from the chaurs was 243.81 kilogram per hectare per year, indicates poor management of capture fishery in chaurs of Bihar in comparison to Bangladesh. It was also observed that the size of captured fishes were small, which indicates the existence of potential to increase the yield from chaur by extending the period of rearing of juvenile fishes.…”
Section: Economics Of Agricultural Crops Produced In Chaurmentioning
confidence: 97%